2015
DOI: 10.1016/j.jff.2014.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Goji berry fruit (Lycium spp.): antioxidant compound fingerprint and bioactivity evaluation

Abstract: The antioxidants in goji berry (Lycium spp.) fruits might confer many health protective benefits by alleviating oxidative stress. The aim of this study was to describe quality traits and the level of potentially bioactive compounds (HPLC fingerprint) and their influence on fruit phytocomplex and antioxidant activity in goji in comparison to the most common fruits. Goji berry was identified as a rich source of antioxidant compounds, with health-promoting properties comparable to other common fruit species.The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
141
5
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(174 citation statements)
references
References 39 publications
16
141
5
12
Order By: Relevance
“…The water is the most suitable solvent for phenolic compounds extraction from goji berry, however, the largest AA values for this fruit extract was found in assay A8, with 19.40 µmol of Trolox/g sample (Table 1). Our results showed lower TPC values than found by Donno et al (2015) in the goji berry from Alzate di Momo in the Northern Italy, who found phenolic compounds levels ranging from 255.87 to 281.81 mg GAE/g sample.…”
Section: Resultscontrasting
confidence: 81%
See 2 more Smart Citations
“…The water is the most suitable solvent for phenolic compounds extraction from goji berry, however, the largest AA values for this fruit extract was found in assay A8, with 19.40 µmol of Trolox/g sample (Table 1). Our results showed lower TPC values than found by Donno et al (2015) in the goji berry from Alzate di Momo in the Northern Italy, who found phenolic compounds levels ranging from 255.87 to 281.81 mg GAE/g sample.…”
Section: Resultscontrasting
confidence: 81%
“…Goji berry, a fruit originated from Asian countries such as China and India, has been used for many years in herbal medicine (Carnés et al, 2013;Donno et al, 2015). This fruit is considered a functional food of great importance for the China and has become increasingly common in the Europe and North America (Li et al, 2007, Dong et al, 2009Carnés et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different bioactive compounds (botanicals) are present in medicinal herbs and derivedproducts as key components (Prabu et al 2012): phenolic compounds, terpenoids, sulfur compounds, vitamins, Electronic supplementary material The online version of this article (doi:10.1007/s13197-015-2115-6) contains supplementary material, which is available to authorized users. pigments, and other natural antioxidants have been associated with protection from and/or treatment of conditions as cardiovascular disease and cancer Donno et al 2014b). All these secondary metabolites are known to be quite variable in the plant material, according to intraspecific chemodiversity, different collection stages or cultivation zone, and post-harvest handling (Prencipe et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Extraction of ethanolic polyphenol was carried out using Donno et al, (2015)with some modification (Donno et al, 2015). 5 g of lyophilized gojiberrry fruit (Benchtop, VirTis, USA) was homogenized 200 ml absolute ethanol and subjected to boiling for 30 min (Polytron, Kinematic AG, Switterzerland) and centrifuged at 6000g for 15 min.…”
Section: Preparation Of Ethanolic Extract Of Goji Berry Polyphenolmentioning
confidence: 99%